Road performance evaluation of prestressed high-strength concrete pile waste powder as alternative filler in asphalt concrete - Tu, Botao; Yang, Xinkui; Xu, Shi; Zhao, Zenggang; Zhou, Yuheng; Jiang, Jian; Fan, Lulu; Tu, Liangliang (Frontiers in Energy Research, 2023)
As a kind of solid waste, using Prestressed High-Strength Concrete Pile Waste Concrete (PPWC) as the replacement for limestone filler in asphalt concrete can not only reduce the accumulation of PPWC and increase its utilization but also avoid the increased road construction costs and environmental degradation associated with limestone mining. This study aims to investigate the effect of using PPWC filler to replace limestone filler on the road performance of asphalt concrete. Firstly, PPWC was ground into filler particles with a diameter less than 0.075 mm. The particle characteristics such as surface morphology, particle size distribution and chemical composition of PPWC filler and limestone filler were compared. Then, PPWC filler was used to replace limestone filler with different volume fractions to prepare asphalt concrete, and the water damage resistance, high-temperature rutting resistance, low-temperature crack resistance, fatigue resistance and adhesion performance of asphalt concrete were tested. The results showed that PPWC filler has a smaller particle size and rougher surface than limestone filler, and it contains Ca(OH)2 produced by hydration. The addition of PPWC filler can effectively improve the mechanical properties of asphalt concrete without reducing its water damage resistance. PPWC filler can improve the high-temperature rutting resistance and low-temperature crack resistance of asphalt concrete, but reduce its low-temperature fatigue resistance. The low content of PPWC filler will enhance the adhesion between asphalt mortar and aggregate. However, when the content of PPWC filler exceeds 50%, Ca (OH)2 in PPWC will reduce the adhesion between acid asphalt mortar and alkaline basalt aggregate. Therefore, the use of PPWC as filler in asphalt mixtures provides a reliable solution for the sustainable development of road materials.